An Approximate Solution of the Space Fractional-Order Heat Equation by the Non-Polynomial Spline Functions - Hasan, Nabaa N.; Salim , Omar H. (Iraqi Journal of Science, 2021)
The linear non-polynomial spline is used here to solve the fractional partial differential equation (FPDE). The fractional derivatives are described in the Caputo sense. The tensor products are given for extending the one-dimensional linear non-polynomial spline to a two-dimensional spline to solve the heat equation. In this paper, the convergence theorem of the method used to the exact solution is proved and the numerical examples show the validity of the method. All computations are implemented by Mathcad15.